'We should classify pet obesity as a disease'. (14th December 2019) - German, Alexander; Ramsey, Ian; Lhermette, Philip
Abstract : Alexander German, Ian Ramsey and Philip Lhermette address some of the concerns raised over calling pet obesity a disease and argue that this classification can bring many management opportunities.